A systematic review of outcome measures in initial rehabilitation of individuals with newly acquired spinal cord injury: providing evidence for clinical practice guidelines - Tomaschek, Rebecca; Gemperli, Armin; Rupp, Rüdiger; Geng, Veronika; Scheel-Sailer, Anke; Baumberger, Michael; Bischoff, Harald; Bothig, Ralf; Domurath, Burkhard; Eisenhuth, Joerg; Fix-Bischoff, Gabriele; Kalke, Yorck; et al. (European journal of physical and rehabilitation medicine, 2019)
INTRODUCTION: A newly acquired spinal cord injury (SCI) has an impact on various aspects of a patients' functioning. Outcome measures represent an important component of initial rehabilitation to assess patients' overall status and their progress. simplify clinical communication and support clinical decision-making. The aim of this review was to create an evidence base for developing clinical practice guidelines using systematic literature review to evaluate assessment instruments used in acute/subacute SCI rehabilitation. EVIDENCE ACQUISITION: PubMed. CINAHL, Cochrane Library and LIVIVO databases were searched using the MeSH terms and key words of the Spinal Cord Injury Research Evidence (SCIRE). Studies on outcome measures with patients in the acute/subacute phase of SCI, published in English or German from January 2013 until December 2018 were included. Two reviewers independently screened articles and when a consensus was not reached two further reviewers were consulted. To determine publication quality of systematic reviews, validation and observation studies, AMSTAR, COSMIN and STROBE checklists were applied. EVIDENCE SYNTHESIS: A total of 2533 records were retrieved. 71 potentially eligible articles identified, and 33 articles finally included. One validation and one observational study met all quality criteria. One systematic review received eight from a maximum of 11 points for publication quality (AMSTAR). Ten of 19 validation studies were deemed as "excellent" or "good" (COSMIN), but some were hampered by the low number of study participants. From the 29 reviewed assessments 28 were recommended and one was not. Seven of 13 observational studies received a rating equal or higher to 20 out of a maximum of 22 points (STROBE). Assessments covered neuro-musculoskeletal, sensory and pain, mental and skin structures and functions, as well as activity, participation and quality of life. CONCLUSIONS: In the field of initial SCI rehabilitation, scientifically sound assessments covering different aspects of the bio-psychosocial model of the ICF are available. According to COSMIN, validation studies struggled with quality, whereas observational studies and systematic studies performed well. The review results support the evidence-based selection of outcome measures for assessing the initial rehabilitation of patients with acute and subacute SCI. These results represent an update for recommendations for clinical guidelines on standardized rehabilitation outcome documentation.
Gesehen am 13.12.2019